2007
DOI: 10.1038/sj.gt.3303088
|View full text |Cite
|
Sign up to set email alerts
|

Single-strand DNA-mediated targeted mutagenesis of genomic DNA in early mouse embryos is stimulated by Rad51/54 and by Ku70/86 inhibition

Abstract: Low and variable efficiency is a major problem in targeted gene alteration, which is used as a primary tool in gene therapy and animal model studies. We tested several types of constructs alone, or in combination with other factors, to introduce a point mutation into the aB-crystallin gene in onecelled mouse embryos. We found that co-injection of ssDNA along with antibodies against Ku70/86, or supplementing the system with hRad51/hRad54, increases efficiency of targeted mutagenesis. These findings suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
4
18
0
Order By: Relevance
“…Similar studies using mouse ova have been conducted to investigate efficiencies of in vivo single-celled embryos gene editing. Attempts to induce targeted point mutations to alter the murine genome via RNA-DNA chimeras, morpholinos (nucleic acid analogs) and single-stranded oligonucleotides to endogenous genes have been somewhat successful but still low (Morozov and Wawrousek, 2008;Tagalakis et al, 2005). Our results with extrachromosomal arrays are consistent with the previous data in germline cells and may suggest that ES cells do not contain sufficient enzymatic activity to promote gene editing unless the reaction is supplemented with pairing proteins or DNA damaging agents (Ferrara and Kmiec, 2004).…”
Section: Gfp47tsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar studies using mouse ova have been conducted to investigate efficiencies of in vivo single-celled embryos gene editing. Attempts to induce targeted point mutations to alter the murine genome via RNA-DNA chimeras, morpholinos (nucleic acid analogs) and single-stranded oligonucleotides to endogenous genes have been somewhat successful but still low (Morozov and Wawrousek, 2008;Tagalakis et al, 2005). Our results with extrachromosomal arrays are consistent with the previous data in germline cells and may suggest that ES cells do not contain sufficient enzymatic activity to promote gene editing unless the reaction is supplemented with pairing proteins or DNA damaging agents (Ferrara and Kmiec, 2004).…”
Section: Gfp47tsupporting
confidence: 93%
“…Despite many microinjection attempts on several of the transgenic strains with varying concentrations of ODNs, no gene editing events were detected. This result is consistent with previous research demonstrating the difficulties encountered in targeting embryonic stem cells and the pronuclei of single-celled embryos in mice (Dekker et al, 2003;Morozov and Wawrousek, 2008;Murphy et al, 2007;Nickerson and Colledge, 2003;Pierce et al, 2003;Tagalakis et al, 2005).…”
Section: Introductionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, this effect could not be recapitulated in chromosomally located reporter systems, 16,23 indicating that in chromosomal targeting integration of the ssODN occurs through mechanisms that are largely independent of transcriptional activity at the target locus. Besides DNA replication and transcription, DNA repair proteins involved in homologous recombination, [34][35][36] and nucleotide excision repair, 37 have also been implicated in the targeting process. However, RNAi-mediated suppression of homologous recombination or nucleotide excision repair protein levels did not affect the targeting frequency in ESCs.…”
Section: Mechanistic Models For Ssodn-mediated Gene Targetingmentioning
confidence: 99%
“…Thus, during naked DNA recombination (i.e., the eGFP extra-chromosomal HR assay), the effect of RAD54 is less profound than that of chromosomal DNA recombination. Morozov and Wawrousek (2007) reported that co-injection of human RAD51 and RAD54 into one-cell mouse embryos additively increases the efficiency of gene targeting. It is suggested that RAD54 promotes HR between the plasmid and chromosome.…”
mentioning
confidence: 98%